What's in a whale bone? Combining new analytical methods, ecology and history to shed light on ancient human-whale interactions. (15th May 2022) - Charpentier, Anne; Rodrigues, Ana S.L.; Houmard, Claire; Lefebvre, Alexandre; McGrath, Krista; Speller, Camilla; van der Sluis, Laura; Zazzo, Antoine; Pétillon, Jean-Marc
Abstract: Ancient human-whale relationships are difficult to study because, counterintuitively, whales have been virtually invisible in the archaeological record despite the immense quantities of valuable products they provide. In this review, we explain the reasons for this invisibility, and we also show how an interdisciplinary approach combining archaeological and ethnographic studies with new biomolecular and isotopic techniques is yielding new insights, allowing a broader perspective on what whale bones found in archaeological sites or collections can tell us. Until recently, the rare whale bones found in archaeological sites were often overlooked or misidentified. The recent development of biomolecular methods, including ancient DNA analyses and collagen peptide mass fingerprinting (ZooMS), has enabled reliable identification of whale species from even small bone fragments. In addition, stable isotope analyses can provide information about ancient whale diets, feeding habits, migrations, or even environmental changes. Combined with radiocarbon dating, these approaches provide valuable ecological and historical context for whale conservation. The results obtained from these new analytical methods can be contextualised by historical and ethnographic information to shed light on ancient uses of whales. Indeed, ethnographic records from maritime cultures around the world reveal that in addition to the bones, whales were valued for their blubber, meat, baleen, intestines, nerves or even veins. Previously undetectable in the archaeological record, recent advances in the analysis of lipid and protein residues, trapped in ceramics or charcoal, can reveal the processing of marine mammal blubber oil in stone pits, the transport of whale products in containers, or the use of blubber for lighting. The identification of the whale species, thanks to ZooMS or ancient DNA analyses, is also essential to consider whether the bone may have originated not simply from scavenging, but through an active capture of the whale, as only some species could be caught with pre-industrial methods. Nonetheless, historical and ethnographic records reveal that a wide diversity of pre-industrial whaling techniques existed throughout the world, beyond the traditional boat and harpoon hunting. The tools they employed, such as natural traps, stone or wooden dams, nets, spears, arrows, and ropes leave few or no artefacts, or artefacts not specific to whaling. Therefore, the absence of unequivocal evidence of whaling should not be confused with evidence that it did not exist. Highlights: Until recently, whales were virtually invisible in the archaeological record. ZooMs and aDNA are revealing whale bones in unexpected archaeological contexts. Lipid residues and stable isotopes are shedding light on past uses of whales. Ethnographic sources show ancient whaling can leave few or no archaeological traces. Knowing the identity of the species is key to judging the plausibility of whaling.